Impact of Resilience and Coping Strategy on Post-Traumatic Symptoms Among Muslim University Students - Kusmawati Hatta; Abizal Muhammad Yati; Azhari Azhari; Muslima Muslima; Syaiful Indra (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2023)
This study examined the association between resilience and coping strategies on post-traumatic stress symptoms in Muslim university students. The study used a cross-sectional design and gathered data from 1157 participants using four questionnaires. The results showed that higher levels of resilience were related to higher coping strategies and lessened post-traumatic stress symptoms. In comparison, higher levels of coping strategies were correlated with lower levels of post-traumatic stress symptoms. In addition, the regression analysis revealed that resilience and coping strategies were significant predictors of post-traumatic stress symptoms, with resilience predicting lower levels of post-traumatic stress symptoms and coping strategies predicting higher levels. These findings suggest that interventions focusing on improving resilience and coping strategies may help reduce post-traumatic stress symptoms among Muslim university students. However, further research is needed to confirm these findings and examine this association's underlying mechanisms.